To expand the expression \((3x + 1)(3x^2 + 7x - 7)\), we will use the distributive property (also known as the FOIL method in the case of binomials).
-
Distribute \(3x\) to each term in the second polynomial: \[ 3x \cdot 3x^2 = 9x^3 \] \[ 3x \cdot 7x = 21x^2 \] \[ 3x \cdot (-7) = -21x \]
-
Distribute \(1\) to each term in the second polynomial: \[ 1 \cdot 3x^2 = 3x^2 \] \[ 1 \cdot 7x = 7x \] \[ 1 \cdot (-7) = -7 \]
-
Combine all the results: \[ 9x^3 + 21x^2 - 21x + 3x^2 + 7x - 7 \]
-
Combine like terms:
- For \(x^2\) terms: \(21x^2 + 3x^2 = 24x^2\)
- For \(x\) terms: \(-21x + 7x = -14x\)
So, the expression simplifies to: \[ 9x^3 + 24x^2 - 14x - 7 \]
The final answer in standard form is: \[ \boxed{9x^3 + 24x^2 - 14x - 7} \]